1999
DOI: 10.1177/135050849961001
|View full text |Cite
|
Sign up to set email alerts
|

Managing Experts and Competing through Innovation: An Activity Theoretical Analysis

Abstract: An activity theoretical analysis is presented of an organization that is operating in a rapidly changing sector and whose competitiveness depends significantly upon the design skills of its engineers. The company designs high-technology make-to-order products. Like other organizations that compete through knowledge and innovation, the prosperity of this company depends upon its organizational learning, that is, upon the effectiveness with which it can mobilize, apply and develop its distinctive knowledge base … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(43 citation statements)
references
References 17 publications
0
42
0
1
Order By: Relevance
“…In their study on the management of innovation, Blackler et al (1999) show that solutions to problems and innovations may also be developed from bottom-up as well as from top-down. Accordingly, they suggest that forums and rules for dialogue in an organisation are needed to promote the articulation of multiple perspectives.…”
Section: Innovation Path Creation and Power Relations In Work Organimentioning
confidence: 99%
See 2 more Smart Citations
“…In their study on the management of innovation, Blackler et al (1999) show that solutions to problems and innovations may also be developed from bottom-up as well as from top-down. Accordingly, they suggest that forums and rules for dialogue in an organisation are needed to promote the articulation of multiple perspectives.…”
Section: Innovation Path Creation and Power Relations In Work Organimentioning
confidence: 99%
“…By using power, implementation can be either promoted or prevented. The aim of this study is to expand our knowledge of power relations (Hardy and Clegg, 1996;Blackler et al, 1999) In the following sections, we first discuss the theoretical concepts of innovation, path creation, agency, and power relations. We then describe the setting and data collection, as well as the methods of analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our own use of activity theory has been to explore the changing nature of expertise in contemporary organisations (Blackler 1993, and Blackler, Crump and McDonald 1999a, 1999b. Generalising from the example of manufacturing industry we have suggested that in some sectors of the economy activity systems are becoming more complex, abstract, interpenetrated and unstable.…”
Section: Power As the Medium Of Responsible Collective Activitymentioning
confidence: 99%
“…Although CHAT is not yet widely known in the U.S., it is being employed by scholar-practitioners across a diverse array of fields to advance ways of thinking about and shaping professional practices such as developing curricula and teaching at all education levels (Cole, 1996;Jonassen & RohrerMurphy, 1999;Roth & Lee, 2007), providing mental health care (Sundet, 2010), strategizing and managing organizational processes (Blackler, Crump, & McDonald, 1999, 2000, designing digital technologies (Kaptelinin & Nardi, 2006), tracing the computerization of architectural design (Groleau, Demers, Lalancette, & Barros, 2012), developing public policy (Canary, 2007(Canary, , 2010Canary & McPhee, 2008), and analyzing work.…”
Section: Introductionmentioning
confidence: 99%